Cognitive Patient Education for Low Back Pain in Primary Care: A Cluster Randomized Controlled Trial and Cost-Effectiveness Analysis. Issue 6 (March 2016) - Werner, Erik L.; Storheim, Kjersti; Løchting, Ida; Wisløff, Torbjørn; Grotle, Margreth
Abstract : Study Design: A pragmatic cluster randomized controlled trial in primary care. Objective: The aim of this study was to estimate the clinical effectiveness and cost-effectiveness of a cognitive-based education program on patients with subacute or chronic low back pain (LBP) in primary care, compared to usual treatment, provided by general practitioners (GP) and physiotherapists (PT). Summary of Background Data: Patient education has been reported to have a favorable effect on patients with chronic musculoskeletal disorders. In this study, an "Explain Pain" model was adapted to fit into an ordinary clinical setting in Norwegian primary care. Methods: Sixteen GPs and 20 PTs participated in the study and a total of 216 patients were recruited. The GPs and PTs were randomly assigned to provide either a cognitive patient education or usual treatment. All patients in both groups were provided with four consultations of 30 min with their provider during the study. In the intervention group the patients were educated according to a specific manual written for the purpose of this study. Results: Eighty-one percent responded at 4-week, and 68% at the 12-month follow-up. There was a substantial improvement in function, pain, and sick leave in both groups. After 4 weeks the intervention group scored 0.51 RMDQ points lower than the control group (Beta –0.506 [95% CI –1.76–0.75]). After 12 months the intervention group scored 0.66 RMDQ points higher than the control group (Beta 0.66 [95% CI −0.56–1.88]). There was no significant difference in QALYs in the two treatment groups; the estimated difference was 0.005 (−0.016–0.027) in favor of the intervention. Conclusion: This study showed no clinical or health economic benefits as a result of adding a cognitive education program to usual treatment for patients with subacute and chronic LBP. Potential weaknesses such as a long recruiting period and potentially low compliance with the cognitive intervention warrant a careful interpretation of the results. Level of Evidence: 3